Instagram and political storytelling among Malaysian politicians during the 14th General Election - Shafizan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The popularity of Instagram as a political tool has world leaders adopting it as an integral part of their communications. Over the recent years, governments and world leaders have flocked to the mobile photo and video sharing social network to share their official as well as personal pictures with a worldwide audience. Malaysian politicians are jumping on the Instagram bandwagon as well. Almost all the prominent politicians have an Instagram account and a significant number of followers. As such, this study explores Instagram’s affordance for visual imageries and political storytelling and its subsequent impact on political communication during election campaign. Methodologically, image analysis was conducted for two months on three Prime Ministerial candidates’ Instagram accounts running up to the historic Malaysian 14th General Election that happened on May 9th, 2018. The result showed that the candidates were actively using Instagram and were uniquely authoring their own stories by switching between narratives that were personal and political. These narratives were presented through six image types that included 1) fieldwork, 2) professionally-produced campaign materials, 3) politician-at-work, 4) family, 5) personal activities and 6) throwbacks. In addition, this analysis offers a crucial look into the mediatization and personalization of politics and contributes to the academic literature on social media, election campaign, as well as political communication in Malaysia.